2014
DOI: 10.1002/ptr.5119
|View full text |Cite
|
Sign up to set email alerts
|

The Neoflavonoid Latifolin Isolated from MeOH Extract ofDalbergia odoriferaAttenuates Inflammatory Responses by Inhibiting NF-κB ActivationviaNrf2-Mediated Heme Oxygenase-1 Expression

Abstract: In Korea and China, the heartwood of Dalbergia odorifera T. Chen is an important traditional medicine used to treat blood disorders, ischemia, swelling, and epigastric pain. In this study, we investigated the inhibitory effects of latifolin, a major neoflavonoid component isolated from the MeOH extract of D. odorifera, on the inflammatory reaction of thioglycollate-elicited peritoneal macrophages exposed to lipopolysaccharide, with a particular focus on heme oxygenase-1 (HO-1) expression and nuclear factor-κB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
57
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 41 publications
2
57
0
Order By: Relevance
“…Together, these data show that LIPC inhibits oxidative stress and inflammation in CI-AKI rats through the suppression of GSK-3β activity. These observations are consistent with other studies also showing that GSK-3β regulates Nrf2 activity [57][58][59][60][61], that Nrf2 has antioxidant effects [54,55,[60][61][62], and that Nrf2-mediated heme oxygenase-1 expression attenuates inflammatory responses by inhibiting NF-κB activation [63,64].…”
Section: Discussionsupporting
confidence: 93%
“…Together, these data show that LIPC inhibits oxidative stress and inflammation in CI-AKI rats through the suppression of GSK-3β activity. These observations are consistent with other studies also showing that GSK-3β regulates Nrf2 activity [57][58][59][60][61], that Nrf2 has antioxidant effects [54,55,[60][61][62], and that Nrf2-mediated heme oxygenase-1 expression attenuates inflammatory responses by inhibiting NF-κB activation [63,64].…”
Section: Discussionsupporting
confidence: 93%
“…HO-1 gene expression is induced by activation of mitogen-activated kinase (MAPKs) that play crucial roles in cellular processes, such as proliferation, apoptosis, and the stress response [5,6]. Recently many studies reported that small molecules, such as resveratrol [7], latifolin [8], sulfuretin [9] and curcumin [10] have inhibitory effects on oxidative stress-induced neuronal damage through induction of HO-1.…”
Section: Introductionmentioning
confidence: 99%
“…The anti-inflammatory effect of DOE may be due to its effects on cellular signaling cascades, as demonstrated in this study. In fact, the neoflavonoid latifolin isolated from a methanol extract of D. odorifera attenuates inflammatory responses by inactivating nuclear factor (NF)-κB through nuclear transcription factor-E2-related factor 2 (Nrf-2)-mediated upregulation of HO-1 [22]. In line with the present finding, isoliquiritigenin, another constituent of D. odorifera , is a powerful anti-inflammatory molecule that protects against the effects of LPS by inhibiting interleukin-1β, tumor necrosis factor-α, and NO production in RAW 264.7 cells [30].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, epigallocatechin-3-gallate and tanshinone IIA stimulate autophagic degradation and endocytic uptake of HMGB1 in RAW264.7 cells, respectively [20, 21]. On the other hand, Dalbergia odorifera , a folk medicinal herb, exhibits a beneficial effect in inflammatory conditions via the induction of heme oxygenase (HO)-1, an anti-inflammatory protein, in murine RAW 264.7 macrophages and BV2 microglial cells [22, 23]. These anti-inflammatory activities of D. odorifera stem from a number of compounds such as flavonoids, phenolic constituents, and quinines isolated from its heartwood [24, 25].…”
Section: Introductionmentioning
confidence: 99%